Analisis Resiko Ergonomi Pada Pekerja Bagian Gudang Menggunakan Metode Resiko Entire Body Assessment (REBA) di PT. Dalwa Anugrah Hasaniyah - Sahroni, Mochamad; Riyana, Iis; Yurniawati, Ratna Diah (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
PT. Dalwa Anugrah Hasaniyah's water production still relies on human power to carry out its production activities. At PT. Dalwa Anugrah Hasaniyah has a section for producing mineral water which is processed manually in a bending and standing position. Activities in the bottle washing section to the machine are (1) inserting labels into bottles, (2) lifting bottles containing water into cartons, and (3) moving cartons containing mineral water to pallets. The activities carried out by workers have a high risk and cause complaints of pain. To overcome this problem, it is necessary to carry out work posture analysis to assess and evaluate worker posture. Based on the results of the Nordic Body Map questionnaire, workers experienced complaints in the waist, spine and secondary areas. The REBA assessment results show the first activity with a score of 6, meaning the activity has a moderate risk of musculoskeletal disorders so improvements need to be made as soon as possible. Meanwhile, the second and third activities have scores of 10 and 11 respectively, which means that these two activities have risks that need immediate action for further investigation and changes.